Transformasi Peran Perpustakaan Universitas Negeri Padang dalam Mendukung Pencapaian Sustainable Development Goals (SDGs) - Aliza, Afadilla Zahra; Nabila, Jeihan (Scinary, 2025)
Padang State University Library is one of the university libraries that has great potential to contribute to the sustainable development goals agenda. The purpose of this research is to analyze the transformation of the role of Padang State University Library in supporting the achievement of Sustainable Development Goals (SDGs). This Research uses a descriptive qualitative approach and data collection techniques such as in-depth interviews, observation, and documentation. In this study, reserachers used data validity testing through triangulation and source triangulation. In this study there were five people as informants consisting of the head of the library and librarians at the Padang State University Library. aThe transformation that has been carried out by the library is reflected in the provision of optimal services, the implementation of information literacy programs, the provision of open access to scientific information sources, and involment in emprowering the academic community and society. The results of this study can be utilized by the library to continue to transform in achieving optimal to support the realization of SDGs.